Power Point-Based Bandicam Development as PGSD Fine Arts Learning Media in Makassar City: Instructional Media - Kartini; Rasmi Nur Anggraeni; Fajriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
This study aims to develop PGSD Visual Arts learning media based on Bandicam and PowerPoint as an effective tool in increasing students' understanding of fine arts. This research involves needs analysis, content design, video production, material processing, and integration with multimedia elements. The research method used is development research by following predetermined steps. The results of this study indicate that PowerPoint-based Bandicam learning media provides a more interactive learning experience for students. Through screen recordings using Bandicam, students can see demonstrations of art techniques, explanations of concepts, and examples of works of art in an attractive format. Integration with multimedia elements such as images, audio, and animation also enhances visual appeal and helps students understand fine art concepts better. Surveys and observations of PGSD Fine Arts students and teachers showed positive results. Students reported that this learning media helped them understand visual art techniques visually and in depth. They also feel actively involved in the learning process. Teachers also reported that this media helped them convey material in a more interesting and interactive way. However, some students indicated a need for more practice and independent use of the media to deepen their understanding. Therefore, it is important for teachers and schools to provide adequate support and guidance to students in using this learning media independently. In conclusion, the development of Bandicam and PowerPoint-based PGSD Visual Arts learning media provides significant benefits in increasing students' understanding of fine arts. This media presents material in an interesting, interactive, and visual way, which helps students gain a deeper understanding. For further development, it is suggested that more practice and self-support be provided for students to meet their needs in deepening their understanding of art.